2022
DOI: 10.3390/v14040790
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of HCV in Russia: Barriers and Perspective

Abstract: Hepatitis C virus (HCV) is highly prevalent in Russia, representing the largest pool of hepatitis C patients in Europe. Effective treatment regimens with direct-acting antivirals can achieve HCV cure in all patients; therefore, in 2016 the World Health Organization proposed eliminating hepatitis C as a public health threat by 2030. However, only a small number of countries are on track to meet the WHO’s hepatitis C elimination targets by 2030 due to many barriers in healthcare systems. This review focuses on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Overall, health systems should adopt strategies to increase testing with community-based hepatitis testing services and provide access to treatment for all grades of fibrosis. In some countries, including Russia, access to treatment is restricted to advanced fibrosis stages [ 26 ]. Lack of a healthcare policy regarding HCV treatment, deficient funding, and poor access to treatment are substantial barriers that must be conquered to reach the elimination of HCV.…”
Section: System-level Barriersmentioning
confidence: 99%
“…Overall, health systems should adopt strategies to increase testing with community-based hepatitis testing services and provide access to treatment for all grades of fibrosis. In some countries, including Russia, access to treatment is restricted to advanced fibrosis stages [ 26 ]. Lack of a healthcare policy regarding HCV treatment, deficient funding, and poor access to treatment are substantial barriers that must be conquered to reach the elimination of HCV.…”
Section: System-level Barriersmentioning
confidence: 99%
“…As shown by the results of a detailed analysis in Lithuania, as many as 41% of cirrhosis patients, 50% of liver cancer patients and 37% of patients requiring liver transplantation were infected with HCV [ 8 ]. However, in light of another work published as part of our Special Issue, the scale of problems related to HCV infections is much greater in Russia, where the most important barriers to HCV elimination are high prevalence of infection, low access to treatment, especially in populations at high risk of HCV infections, and centralization of the healthcare system, making linkage to care difficult [ 9 ].…”
Section: Testing and Linkage To Carementioning
confidence: 99%
“…It has been shown that the incidence of hepatocellular carcinoma (HCC) increases 15–20 times in patients with CVHC [ 2 ]. Despite advances in treatment, the problem of CVHC remains very relevant due to the remaining significant pool of patients [ 3 , 4 ]. The most common CVHC genotypes in Russia are the first (56.6%) and the third (35.4%) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%